Research on Spatiotemporal Evolution and Driving Factors of Extreme Climate in Guangdong-Hong Kong-Macao Greater Bay Area - GUO Shan; ZHANG Dawei; WANG Yadi (Renmin Zhujiang)
In recent years,frequent extreme climate events have become the focus of attention of the world.Studying the spatiotemporal evolution of extreme climate in the Guangdong-Hong Kong-Macao Greater Bay Area is of great significance for timely and accurate disaster prevention and mitigation forecasts and early warnings.On the basis of the precipitation and temperature data from 1961 to 2016,this paper uses the heuristic segmentation method,Mann-Kendall trend test,and cross wavelet method to analyze the spatiotemporal evolution of extreme climate in the Guangdong-Hong Kong-Macao Greater Bay Area and its relationship with driving factors.The results reveal that extreme precipitation and temperature changes are potentially related to sunspots and large-scale circulation factors including the multivariate ENSO index (MEI) and interdecadal Pacific oscillation (IPO),but their effects on extreme climate are different.Climate change will continue to profoundly affect urban construction and development.For future studies on the climate change in the Guangdong-Hong Kong-Macao Greater Bay Area,attention should be paid to the impact assessment of climate change in the Pearl River Basin and typical regions,and the research on the occurrence mechanism,risk assessment,countermeasures of extreme weather in the basin should be strengthened to reduce the damage of extreme climate events.